Efeito do estresse mineral induzido por fontes e doses de potássio na produção de raízes em plantas de berinjela (Solanum melongena L.) - Marques, Douglas Jose [UNESP] (2010)
This study was carried out at the Department of Plant Production, Sector Horticulture, São Paulo State University-UNESP, Botucatu Campus, São Paulo State, Brazil in order to evaluate the effect of sources and increasing doses of potassium in roots of eggplant. The experimental design was randomized blocks in factorial scheme 2 x 4 (two sources of potassium: KCl and K(2)SO(4) and four doses of K(2)O, 250, 500, 750 and 1000 kg ha(-1)) and three replications. For the experiment, we used Oxisol medium texture (615 g of sand, 45 g of silt and 340 g of clay per kg soil). The soil passed through sieve of 5 mm and packed in plastic pots with a capacity of 32 liters of soil where plants were grown. The pots were distributed with a spacing of 0,63 m between plants and 1,0 m between rows each pot being grown with a plant. The evaluated characteristics were: root dry mass and volume of the root. It was concluded that sources and excessive doses of mineral K(2)O induces stress in eggplants and affect the roots being less harmful K(2)SO(4) source.